MEMPERKUAT AKUNTABILITAS: DAMPAK TATA KELOLA PERUSAHAAN YANG BAIK TERHADAP PELAPORAN AUDIT YANG TEPAT WAKTU (Strengthening Accountability: Good Corporate Governance's Influence On Timely Audit Reporting) - Aulia, Chania; Triyono, Triyono; Setiawati, Erma (STIE Atma Bhakti, 2024)
A number of academics have focused their research on the effect of corporate governance on audit report lag. With varying levels of significance, the studies that havebeen conducted show mixed findings, both consistent and otherwise. The purpose of this study is to collect information from journals regarding corporate governance issuesthat affect audit report lag in Indonesia from 2009 to 2022. The research sample consisted of 23 documents, including journals and university students' theses, which were purposively selected. The researcher combined the journal research results withthe meta-analysis method. This study shows that the board of commissioners, independent commissioners, and audit committee significantly affect audit delay. Theaverage correlation value of less than 0.25 indicates that the correlation between the independent and dependent variables is relatively low. In addition, this study confirmed the agency theory in the period 2009-2022 for various business industries, includingbanking, manufacturing, and LQ45 index stocks.